Familial hypercholesterolaemia - the Cape Town experience - Firth, Jean Catherine (Department of Medicine, 2024)
This dissertation is a descriptive study of 1029 patients with familial hypercholesterolaemia attending a referral clinic for severe dyslipidaemia. The author was involved in patient management and clinical research over a period of almost 20 years. Information for the thesis was extracted from patient records and expanded to include data obtained from a routine as well as a research lipid laboratory. Data were analysed using conventional statistical methods. The thesis reviews familial hypercholesterolaemia from its original description to current opinions. A historical perspective, with particular emphasis on South African founder effects is given. Lipoprotein metabolism is briefly reviewed to enable a better understanding of the pathology and complications of the disease. Demographics of patients attending the clinic, their clinical signs, lipid profiles and complications are analysed in the context of different ethnic origins and genetic defects. Lipoproteins, especially low density lipoprotein particle size, were examined in detail, with particular reference to the risk of ischaemic heart disease. Factors known to influence low density lipoprotein size in normals were examined. Body mass, age, gender and triglyceride concentration all had the expected effects. Carotid intima media thickness was examined to ascertain whether it could discriminate between early and late onset of heart disease in middle-aged subjects with familial hypercholesterolaemia. Patient management and response to treatment was analysed in the context of gender, lifestyle, ethnic origin, lipid profile and genotype. Familial hypercholesterolaemia in Cape Town identifies high risk individuals with an average age of cardiovascular complications of 43 years in men and 49 years in women. Average age of death in 1994 was 48 years, this improved to 55 years by 2001, presumably as a consequence of statin treatment. In the study cohort, 46% had an identified genotype, varying from 94% in the Asian population to 24% in patients with mixed ancestry. The first description of a geographic distribution of Afrikaners with familial hypercholesterolaemia is given. This regional variation might relate to migration of early settlers away from the Cape. Null defects of the low density lipoprotein receptor resulted in worse biochemical and clinical effects whilst variation in low density lipoprotein size did not appear to confer additional risk. Patients with very premature ischaemic heart disease tended to smoke more, had lower high density lipoprotein and higher low density lipoprotein, but did not have thicker intima media thickness.